A conceptual approach to characterizing ecological suitability: Informing socio-ecological measures for restoration effectiveness. (October 2022) - Smith, Lisa M.; Reschke, Erin M.; Bousquin, Justin J.; Harvey, James E.; Kevin Summers, J.
Highlights: The ecological suitability approach builds upon previous restoration frameworks. The conceptual approach is applicable to multiple ecosystem types. A balance of ecological and social outcomes for targeted restoration is promoted. Ecological suitability is a novel way to communicate potential restoration outcomes to ecosystem managers and stakeholders. Abstract: A combination of ecological and socio-economic outcome indicators is essential for understanding and assessing the effectiveness of the remediation and restoration of degraded ecosystems and revitalizing communities that could benefit from these ecosystem management activities. In this paper, we propose and develop a conceptual approach to characterize ecological suitability that incorporates ecological attributes that support ecosystem structural diversity and functionality, stakeholder values and perceptions, and the benefits derived from ecosystem goods and services. A structured literature review was used to identify existing restoration frameworks and indicators to inform the conceptual foundation for characterizing ecological suitability. The structure of the conceptual approach primarily builds from ecological and social attributes in the International Principles and Standards for the Practice of Ecological Restoration (Gann et al., 2019 ). We provide a conceptual example of the ecological suitability approach in estuaries. This example is based on habitat suitability and food web characterizations in combination with the provisioning of ecosystem services and desired social benefits to prioritize and evaluate restoration effectiveness. This foundational work sets the stage for developing a composite measure of ecological suitability. The holistic conceptual approach presented complements existing information regarding restoration effectiveness evaluations. Characterizing ecological suitability is a novel way to incorporate ecological and social information and communicate potential restoration outcomes to ecosystem managers and stakeholders.